Physical Tunning Influence on 4G Network in Minangkabau International Airport - Yuhanef, Afrizal; Chandra, Dikky; Mursydan, Arif; Zurnawita; Yusnita, Sri (International Journal of Advanced Science Computing and Engineering, 2023)
The growth of cellular telephone subscribers experienced a significant increase compared to other industries. With large and widespread number of subscribers, many operators have established new Base Transceiver Stations (BTS) to keep up with the increase number of subscribers. However, the addition of BTS is not a total solution to offset the increase number of subscribers. The purpose of this study is to analyze the signal quality, coverage area and network repairs by using physical tuning method. In Telkomsel operator drive test data in Minangkabau International Airport area, the RSRP parameter obtained an average sample data area around the site in the range -110 to 0, with a red indicator of 3.35%, an orange indicator of 18.96% and a yellow indicator amounted 36.3%. In this way, this research optimizes physical tuning method, including Re-azimuth which successfully directs the antenna to the badspot area, then changes the height of the antenna which makes it covered farther and tilting the Antenna which succeeds in making the coverage area more optimal. For the next bad spot area, optimization should be done in real time in the field so that the improvement can be resolved properly.